Systematic Managed Float for Exchange Rate Works or Not? Evidence from Turkey - Bayat, Tayfur; Tasar, İzzet (My University, 2026)
This study examines the dynamics of structural breaks in Turkey's foreign exchange market and exchange rate regimes using the index of foreign exchange market pressure (EMP) from January 2006 to October 2024. The low negative correlation between the nominal exchange rate and central bank reserves suggests a managed exchange rate regime during this period. The cointegration model with structural breaks identifies three key breaks: November 2008 (global financial crisis), February 2012 (European debt crisis), and February 2022 (post- pandemic economic transformation). From January 2006 to October 2008, a market-oriented floating exchange rate regime was in place. After November 2008, foreign exchange market interventions increased due to the global crisis, deviating from the floating exchange rate regime. Between February 2012 and January 2022, EMP peaked, and policies resembling a fixed exchange rate regime were pursued. In the most recent period (February 2022 to October 2024), foreign exchange interventions decreased, but exchange rate uncertainties remained. Furthermore, post-January 2022, the Japanese Yen was not used for arbitrage. Policy recommendations include strengthening the floating exchange rate regime, better management of foreign exchange reserves, and using reserves only during crises
Keywords: Central bank; foreign exchange market pressure index; exchange rate regimes; Cointegration with structural breaks